2010
DOI: 10.1111/j.1365-2125.2010.03743.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary efficacy and safety of an oromucosal standardized cannabis extract in chemotherapy‐induced nausea and vomiting

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Orally administered synthetic cannabinoids (nabilone and dronabinol) have been shown to be superior to dopamine receptor antagonists in preventing chemotherapy-induced nausea and vomiting (CINV).• There is no information on the tolerability of an acute dose titration of a whole-plant cannabis-based medicine (CBM).• The efficacy of cannibidiol with tetrahydrocannabinol added to the current standard therapy in the control of CINV after moderately emetic cancer chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 17 publications
1
61
0
4
Order By: Relevance
“…Numerous studies, most of them carried out in the 1970s and 1980s, have demonstrated that cannabinoids are equally or more effective in treating chemotherapy-related nausea and vomiting as the standard antiemetics (15,16,17). Some studies have shown that cannabis is effective in the treatment of anorexia and cachexia in patients with human immunodeficiency virus (HIV) (18), tumours (19) and Alzheimer's disease (20), as well as in the treatment of chronic neuropathic pain and multiple sclerosis (21,22).…”
Section: Erapeutic Potential Of Cannabismentioning
confidence: 99%
“…Numerous studies, most of them carried out in the 1970s and 1980s, have demonstrated that cannabinoids are equally or more effective in treating chemotherapy-related nausea and vomiting as the standard antiemetics (15,16,17). Some studies have shown that cannabis is effective in the treatment of anorexia and cachexia in patients with human immunodeficiency virus (HIV) (18), tumours (19) and Alzheimer's disease (20), as well as in the treatment of chronic neuropathic pain and multiple sclerosis (21,22).…”
Section: Erapeutic Potential Of Cannabismentioning
confidence: 99%
“…Conditioned retching in S. murinus and conditioned gaping in the rat induced by the context (signs of anticipatory vomiting and nausea, respectively) were also reduced by CBD [53,56]. All these data suggest that CBD might be a useful non-psychotropic CB alternative to control nausea and emesis in humans too; to our knowledge, it has not been tested on its own for this, but the effects are positive when combined with THC [40]. …”
Section: Cb Effects On Altered Gi Motilitymentioning
confidence: 99%
“…Different CBs (THC and nabilone, its synthetic analogue) and CB extracts (containing both THC and CBD) have proved to be effective anti-emetics in humans [39,40]. Moreover, CBs exert antinauseant effects [41].…”
Section: Cb Effects On Altered Gi Motilitymentioning
confidence: 99%
“…32 The overall observation included early (0-24 hours) and delayed (24-120 hours) phase periods. This study included a heterogeneous population in terms of type of cancer and the chemotherapeutic agents used.…”
mentioning
confidence: 99%